The Analysis of Financial Reporting in Ministries/State Institutions and Supervision of BUMN for Transparency & Accountability - Nurwenda, Mirna; Junaedi, Dedi (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to analyze financial reporting in ministerial institutions and BUMN supervision for transparency and accountability. The Ministry/Institution was established to serve the community, as a Public Service Agency (BLU), therefore it is non-profit oriented organization, while its subsidiary, namely BUMN, operates to seek profit. So there are different accounting standards in regulating both, namely governmental accounting standards and Financial Accounting Standards that regulate BUMN financial reporting. The research method used is descriptive and verificative. Descriptive research is conducted by accessing the website of each ministry/state institution and local government agency. Verification research by distributing questionnaires to officials of Bappenas and to BPKP auditors. The result is the financial reporting variable, transparency and accountability have not been fully fulfilled by the Government Institution according to applicable regulations. The BUMN supervision variable has been implemented well, the BPKP auditors have worked professionally. Our suggestion is to revise the explanation/attachment of the Regulation of the Minister of Finance and the Minister of Home Affairs regarding BLU financial reporting so that the contents are in sync with its attachments